Effects of traditional judo training session on muscle damage symptoms - Detanico, D.; Dal Pupo, J.; Franchini, E.; Fukuda D. H.; dos Santos, S. G. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: This study aimed to analyze the acute effects of a judo training session on muscle strength, delayed-onset muscle soreness (DOMS), and serum creatine kinase (CK) activity.